2010
DOI: 10.1111/j.1756-5391.2010.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for drug resistance in pulmonary tuberculosis inpatients

Abstract: Objective To analyze risk factors for drug resistance in pulmonary tuberculosis (PTB) ]).Conclusions A history of drug treatment is associated with drug resistance among PTB inpatients. Initial resistance becomes increasingly serious till 2007. To minimize the development of resistance, more personalized treatment and supervision should be used, and better training for medical staff is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Previous TB treatment, a well-known risk factor for drug-resistant TB [7] [9]- [11] [14] [15] was also found to be significantly associated with drug resistance in the present study. Although drug-resistant TB can be transmitted between individuals (primary resistance), most cases arise after inadequate treatment allowing a drug-resistant strain to become dominant [10].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Previous TB treatment, a well-known risk factor for drug-resistant TB [7] [9]- [11] [14] [15] was also found to be significantly associated with drug resistance in the present study. Although drug-resistant TB can be transmitted between individuals (primary resistance), most cases arise after inadequate treatment allowing a drug-resistant strain to become dominant [10].…”
Section: Discussionsupporting
confidence: 63%
“…International studies have identified various risk factors for drug-resistant TB; these include previous TB treatment, poor adherence to treatment regimens, inadequate regimens and positive smear result at the end of the second and third month of treatment [7]- [17]. In addition of these programmatic factors, patients characteristics such as HIV co-infection, alcohol abuse and younger age [7]- [14] are also believe to influence the drug resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that inadequate treatment of MDR-TB is a severe problem in China, particularly in hospitals [5,24]. Thus, it has become a common belief that patients who have a previous history of anti-TB treatment are most likely to develop drug resistance [13,2527]. This study confirmed that the risk of developing MDR-TB was 2 to 11 times higher amongst TB patients who were in the five high-risk groups than amongst patients who were not.…”
Section: Discussionmentioning
confidence: 99%
“…While repeated inadequate tuberculosis (TB) treatment courses represent the most important risk factor for developing MDR-TB, new patients may also be diagnosed with MDR-TB as a result of the transmission of resistant strains 2 . Late diagnosis, as a consequence of limited access to diagnostic services, and the poor socioeconomic conditions of many patients are factors that contribute to the development of resistant strains 3 …”
Section: Introductionmentioning
confidence: 99%